"Station-Sequence" parts feeding in mixed models assembly: Impact of variations and industry 4.0 possible solutions. Issue 2 (2020) - Bortolini, M.; Faccio, M.; Gamberi, M.; Pilati, F.
Abstract: Parts feeding is a complex logistic problem, stressed by the increasing product variety that forces the assembly systems to manage a great number of models with a mixed model approach. In this context a possible parts feeding policy is the "station-sequence", sequences of parts supplied to the assembly stations as function of the production models. This parts feeding policy can reduce stocks at the assembly stations, but offers potential production stops due to its low robustness. Different external elements can perturb the parts sequences (i.e. changing in production schedule, tasks times variation, variable supply lead times, etc.). The aim of this paper is to study, through a simulation study and a statistical analysis, the station-sequence part feeding policy considering its dynamic time-dependence the impact of the model mix and time perturbations on the system performance. Authors discuss the possible application of the real time events traceability, achievable through the I4.0 application, in order to mitigate the variability influence on the system performances.